STRATEGI APOLOGI DALAM WACANA PERCAKAPAN DI BALAI DIKLAT KEAGAMAAN SURABAYA - Jamal Jamal (LITERA, 2010)
This study aims to explain apology types and strategies in conversationaldiscourses in the Religious Training Office Surabaya. The data sources were people involved in the training activities, including tutors/lecturers and participants. The data were collected through participant observations, in-depth interview, and documents. The data were analyzed by means of the interactive, simultaneous, and continuous technique developed by Miles and Huberman. The data analysis activities included (1) data reduction, data display, and conclusion drawing/inference. The findings are as follows. First, the anticipatory apology appears as frequently as the remedy apology. Apologies are stimulated by elements of space, time, speech, inability, and strength. Second, apologies contain explicit excuses with reasons in order to reduce linguistic and non-linguistic malfunctions. Third, strategies employed in apologies are varied, depending on the purposes.